Anti-dazzle hardened film and electronic equipment

By adding a wear-resistant layer on the surface of the anti-glare layer of the anti-glare film and controlling the ratio of the protruding height of the organic particles to the thickness of the wear-resistant layer, the problem of insufficient wear resistance of the anti-glare film is solved, and low haze and high definition are achieved It also significantly improves wear resistance while excellent anti-glare effect.

CN119200056APending Publication Date: 2024-12-27NINGBO HUGHSTAR ADVANCED MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411614335.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing anti-glare films are prone to wear during use, which is difficult to meet the high requirements of users for wear resistance.

Method used

By adding a wear-resistant layer on the surface of the anti-glare layer and controlling the ratio of the minimum protrusion height of the organic particles to the thickness of the wear-resistant layer is between 1.5 and 2.0, a suitable concave-convex structure is formed to improve the overall wear-resistant performance and anti-glare effect. .

Benefits of technology

It achieves low haze, high definition and excellent anti-glare effect of the anti-glare hardened film, while significantly improving wear resistance and able to withstand 2,000 scratch-free friction tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119200056A_ABST
    Figure CN119200056A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides an anti-dazzle hard coating film and electronic equipment, and relates to the field of optical protection films. The anti-dazzle hard coating film comprises a base material layer, an anti-dazzle layer and a wear-resistant layer which are sequentially stacked from bottom to top, the anti-dazzle layer contains organic particles, and the upper half parts of the organic particles protrude and are embedded into the wear-resistant layer; the thickness of the anti-dazzle layer is H1, the thickness of the wear-resistant layer is H2, the diameter of the organic particles is D, # imgabs0 #, and X is equal to 1.5-2.0. The anti-dazzle hard coating film and the electronic equipment provided by the embodiment of the invention have excellent anti-dazzle effect and wear resistance at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of optical protective films, and more specifically, to an anti-glare hardened film and electronic equipment. Background Art

[0002] Anti-glare film can effectively reduce the reflection of ambient light and improve the clarity and contrast of the display image, so it is widely used in various electronic devices such as mobile phones, tablets, TVs, etc. However, anti-glare film is often exposed to contact and friction during use, and its surface is easily worn, affecting its use effect and life. The surface wear resistance of current anti-glare film is difficult to meet the higher requirements of users.

[0003] Therefore, how to improve the wear resistance of anti-glare films is an urgent problem to be solved in the current field of optical film preparation technology. Summary of the invention

[0004] The purpose of the embodiments of the present application is to provide an anti-glare hardened film and an electronic device, which have both excellent anti-glare effect and wear resistance.

[0005] In a first aspect, an embodiment of the present application provides an anti-glare hardened film, which includes a substrate layer, an anti-glare layer (AG layer) and a wear-resistant layer (HC layer) stacked in sequence from bottom to top, the anti-glare layer contains organic particles, the upper half of the organic particles protrude and are embedded in the wear-resistant layer; the thickness of the anti-glare layer is H1, the thickness of the wear-resistant layer is H2, the diameter of the organic particles is D, And X=1.5~2.0.

[0006] In the above technical solution, a wear-resistant layer is added on the surface of the anti-glare layer to improve the overall wear resistance; and by controlling the ratio of the minimum protruding height D-H1 of the organic particles in the anti-glare layer to the thickness H2 of the wear-resistant layer The anti-glare hardened film as a whole has low haze, high definition, excellent anti-glare effect and wear resistance.

[0007] Specifically, after the anti-glare coating corresponding to the anti-glare layer is coated, the organic particles have a floating phenomenon, that is, the floating height of the organic particles in the formed anti-glare layer is ≥ D-H1. If the ratio X is too high, it means that the difference between the minimum protruding height of the organic particles and the thickness of the wear-resistant layer is too large, that is, the floating height of the organic particles relative to the anti-glare layer is too large. On the one hand, it may indicate that the haze of the anti-glare hardened film is high and the anti-glare property is too strong, which will reduce the visual clarity and reduce the contrast and resolution of the electronic device screen. On the other hand, it indicates that the surface roughness of the anti-glare hardened film is too large, which will reduce the wear resistance. If the ratio is too low, it means that the thickness of the wear-resistant layer is close to or higher than the minimum protruding height of the organic particles, that is, the floating height of the organic particles relative to the anti-glare layer is too small or does not float. Although the anti-glare hardened film may have excellent wear resistance, it has almost no anti-glare performance.

[0008] In a possible implementation, the haze of the anti-glare layer is 50-90%, and can be 60-80%;

[0009] And / or, the clarity of the anti-glare layer is 30-100%, optionally 40-90%, further optionally 50-80%;

[0010] And / or, the haze of the anti-glare hardened film is 1 to 6%;

[0011] And / or, the clarity of the anti-glare hardened film is 250-450%.

[0012] In the above technical solution, if the clarity of the anti-glare layer is too low and the haze is too high, the anti-glare property will be too strong, which may cause flash points in the coating film; if the clarity of the anti-glare layer is too high, the clarity will be greatly improved after adding a wear-resistant layer, resulting in the final finished product surface not having anti-glare properties.

[0013] In a possible implementation, the material of the organic particles includes one or more of polyacrylate, polystyrene, and polymethacrylate;

[0014] And / or, the average particle size of the organic particles is 2 to 5 μm.

[0015] In the above technical solution, the anti-glare layer has an anti-glare effect through particles, organic particles are used to meet the clarity requirements, and the particle size of the organic particles is screened so that the surface of the anti-glare hardened film has sufficient concave-convex structure to provide haze and anti-glare properties.

[0016] In a possible implementation, the thickness H1 of the anti-glare layer is 0.5-3 μm, and the thickness H2 of the wear-resistant layer is 0.3-2 μm.

[0017] In the above technical solution, by selecting a suitable film thickness, the surface of the anti-glare hardened film has a sufficient concave-convex structure to provide haze and anti-glare properties.

[0018] In a possible implementation, the formula of the anti-glare coating corresponding to the anti-glare layer includes, by weight: 20 to 40 parts by weight of polyurethane acrylate; 1 to 10 parts by weight of organic particles; 1 to 5 parts by weight of photoinitiator; 0.1 to 1 parts by weight of leveling agent; 1 to 5 parts by weight of dispersant; and 40 to 70 parts by weight of organic solvent.

[0019] In a possible implementation, the functionality of the polyurethane acrylate is 2 to 10, and the molecular weight is 1000 to 20000;

[0020] The photoinitiator includes one or more of 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, benzoin dimethyl ether, xylene ketone, 2-isopropylthioxanthone, 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide, and TPO;

[0021] The organic solvent includes one or more of ethyl acetate, butyl acetate, methyl ether, propylene glycol methyl ether, methyl isobutyl ketone, butanone, cyclohexanone, n-butanol, n-propanol, isopropanol, toluene and xylene.

[0022] In a possible implementation, the formula of the wear-resistant coating corresponding to the wear-resistant layer includes, by weight: 10 to 40 parts by weight of polyurethane acrylic resin; 1 to 10 parts by weight of inorganic particles; 1 to 5 parts by weight of photoinitiator; 0.1 to 2 parts by weight of leveling agent; and 60 to 90 parts by weight of organic solvent.

[0023] In a possible implementation, the functionality of the polyurethane acrylic resin is 6 to 15, and the molecular weight is 1000 to 20000;

[0024] The inorganic particles include one or more of silicon dioxide, aluminum oxide, zinc oxide, magnesium oxide, calcium carbonate, magnesium carbonate, aluminum hydroxide and titanium dioxide, and the average particle size of the inorganic particles is 1 to 100 nm;

[0025] The photoinitiator includes one or more of 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, benzoin dimethyl ether, xylene ketone, 2-isopropylthioxanthone, 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide, and TPO;

[0026] The organic solvent includes one or more of ethyl acetate, butyl acetate, methyl ether, propylene glycol methyl ether, methyl isobutyl ketone, butanone, cyclohexanone, n-butanol, n-propanol, isopropanol, toluene and xylene.

[0027] In a possible implementation, the material of the substrate layer includes one or more of polyethylene terephthalate resin, polycarbonate, triacetyl cellulose and polymethyl methacrylate;

[0028] And / or, the thickness of the substrate layer is 25 to 200 μm.

[0029] In a second aspect, an embodiment of the present application provides an electronic device, comprising the anti-glare hardened film provided in the first aspect, wherein the anti-glare hardened film is disposed on a screen surface of the electronic device, and the wear-resistant layer faces upward.

[0030] In the above technical solution, the anti-glare hardened film has excellent anti-glare effect and wear resistance, meeting the user's requirements for the use of electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 A schematic diagram of the structure of an anti-glare hardening film provided in an embodiment of the present application.

[0033] Icon: 110 - base material layer; 120 - anti-glare layer; 121 - organic particles; 130 - wear-resistant layer. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0035] The anti-glare hardened film and the electronic device according to the embodiments of the present application are described in detail below.

[0036] Please see Figure 1 The embodiment of the present application provides an anti-glare hardened film, which includes a substrate layer 110, an anti-glare layer 120 (AG layer) and a wear-resistant layer 130 (HC layer) stacked in sequence from bottom to top, the anti-glare layer 120 contains organic particles 121, the upper half of the organic particles 121 protrudes and is embedded in the wear-resistant layer 130; the thickness of the anti-glare layer 120 is H1, the thickness of the wear-resistant layer 130 is H2, and the diameter of the organic particles 121 is D, And X=1.5~2.0.

[0037] In order to facilitate the description of the stacking order of each layer, this application adopts the "bottom-to-top" direction for description, and does not limit the setting direction of the anti-glare hardened film after use. From the "bottom-to-top" direction, part of the organic particles 121 protrudes relative to the anti-glare layer 120 and is embedded in the wear-resistant layer 130, and at least part of the number of organic particles 121 also protrudes relative to the wear-resistant layer 130.

[0038] In some embodiments of the present application, the haze of the anti-glare layer 120 is 50-90%, and may be 60-80%; and / or the clarity of the anti-glare layer 120 is 30-100%, and may be 40-90%, and may be 50-80%;

[0039] And / or, the haze of the antiglare cured film is 1 to 6%; and / or, the clarity of the antiglare cured film is 250 to 450%.

[0040] In some embodiments of the present application, the material of the organic particles 121 includes one or more of polyacrylate, polystyrene, and polymethacrylate; exemplarily, the organic particles 121 are one of polyacrylate microspheres, polystyrene microspheres, polymethacrylate microspheres, and polystyrene-polymethacrylate (PSA-PMMA) composite microspheres.

[0041] And / or, the average particle size D of the organic particles 121 is 2 to 5 μm.

[0042] In some embodiments of the present application, the thickness H1 of the anti-glare layer 120 is 0.5-3 μm, and the thickness H2 of the wear-resistant layer 130 is 0.3-2 μm.

[0043] The present application does not specifically limit the composition of the anti-glare layer 120, and the composition design of the anti-glare layer 120 well known to those skilled in the art can be adopted. In some embodiments of the present application, the formula of the anti-glare coating corresponding to the anti-glare layer 120 includes, by weight: 20 to 40 parts by weight of polyurethane acrylate; 1 to 10 parts by weight of organic particles 121; 1 to 5 parts by weight of photoinitiator; 0.1 to 1 parts by weight of leveling agent; 1 to 5 parts by weight of dispersant; and 40 to 70 parts by weight of organic solvent.

[0044] For each raw material of the anti-glare coating, the functionality of the polyurethane acrylate is 2 to 10, and the molecular weight is 1000 to 20000;

[0045] The photoinitiator includes one or more of 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, benzoin dimethyl ether, xylene ketone, 2-isopropylthioxanthone, 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide, and TPO;

[0046] The organic solvent includes one or more of ethyl acetate, butyl acetate, methyl ether, propylene glycol methyl ether, methyl isobutyl ketone, butanone, cyclohexanone, n-butanol, n-propanol, isopropanol, toluene and xylene.

[0047] The present application does not specifically limit the composition of the wear-resistant layer 130, and the composition design of the wear-resistant layer 130 well known to those skilled in the art can be adopted. In some embodiments of the present application, the formula of the wear-resistant coating corresponding to the wear-resistant layer 130 includes, by weight: 10 to 40 parts by weight of polyurethane acrylic resin; 1 to 10 parts by weight of inorganic particles; 1 to 5 parts by weight of photoinitiator; 0.1 to 2 parts by weight of leveling agent; and 60 to 90 parts by weight of organic solvent.

[0048] For each raw material of the wear-resistant coating, the functionality of the polyurethane acrylic resin is 6 to 15, and the molecular weight is 1000 to 20000;

[0049] The inorganic particles include one or more of silicon dioxide, aluminum oxide, zinc oxide, magnesium oxide, calcium carbonate, magnesium carbonate, aluminum hydroxide and titanium dioxide, and the average particle size of the inorganic particles is 1 to 100 nm;

[0050] The photoinitiator includes one or more of 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, benzoin dimethyl ether, xylene ketone, 2-isopropylthioxanthone, 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide, and TPO;

[0051] The organic solvent includes one or more of ethyl acetate, butyl acetate, methyl ether, propylene glycol methyl ether, methyl isobutyl ketone, butanone, cyclohexanone, n-butanol, n-propanol, isopropanol, toluene and xylene.

[0052] The present application does not specifically limit the material of the substrate layer 110, and the material of the transparent substrate layer 110 well known to those skilled in the art can be used. In a possible implementation, the material of the substrate layer 110 includes one or more of polyethylene terephthalate (PET) resin, polycarbonate (PC), triacetyl cellulose (TAC) and polymethyl methacrylate (PMMA). Exemplarily, the transparent substrate layer 110 is one of a polyethylene terephthalate resin base film, a polycarbonate base film, a triacetyl cellulose base film and a polymethyl methacrylate base film, and specifically can be a polyethylene terephthalate resin base film.

[0053] And / or, the thickness of the base layer 110 is 25 to 200 μm.

[0054] In the embodiment of the present application, a thinner wear-resistant layer 130 is coated on the anti-glare layer 120 to form a specific concave-convex structure to optimize the surface wear resistance, which not only ensures that the anti-glare hardened film has excellent anti-glare properties and high clarity, but also greatly improves the wear resistance.

[0055] In some embodiments of the present application, the method for preparing the anti-glare hardened film comprises the following steps:

[0056] Preparation of anti-glare coating: add 1 to 10 parts by weight of organic particles 121 to 20 to 40 parts by weight of polyurethane acrylate, add 40 to 70 parts by weight of organic solvent, 1 to 5 parts by weight of photoinitiator, 0.1 to 1 part by weight of leveling agent, and 1 to 5 parts by weight of dispersant, and mix well to obtain anti-glare coating.

[0057] Preparation of wear-resistant coating: add 1 to 10 parts by weight of inorganic particles to 10 to 40 parts by weight of polyurethane acrylic resin, add 60 to 90 parts by weight of organic solvent, 1 to 5 parts by weight of photoinitiator, and 0.1 to 2 parts by weight of leveling agent, mix well to obtain wear-resistant coating.

[0058] First, an anti-glare coating is applied on one side of the substrate layer 110 and then subjected to photocuring to form an anti-glare layer 120 ; then, an abrasion-resistant coating is applied on the surface of the anti-glare layer 120 and then subjected to photocuring to form an abrasion-resistant layer 130 , thereby obtaining an anti-glare hardened film.

[0059] An embodiment of the present application also provides an electronic device, which includes the anti-glare hardened film of the aforementioned embodiment, and the anti-glare hardened film is arranged on the screen surface of the electronic device with the wear-resistant layer facing upward.

[0060] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0061] Examples and Comparative Examples

[0062] Each embodiment and comparative example provides an anti-glare hardened film, and the preparation process is as follows:

[0063] (1) Preparation of anti-glare coating:

[0064] The following raw materials are mixed evenly to obtain an anti-glare coating.

[0065] Polyurethane acrylate (product name "L-6606", Lankelu): 30 parts by weight;

[0066] Organic particles: 2 parts by weight; wherein the organic particles in Examples 1 to 2, Comparative Examples 1 to 2, and Comparative Examples 5 to 6 are SX-350H from Soken Chemical; the organic particles in Example 3 and Comparative Examples 3 to 4 are SX-500H from Soken Chemical; the organic particles in Example 4 are SX-200H from Soken Chemical;

[0067] Photoinitiator (product name "Irgacure 184", BASF): 2 parts by weight;

[0068] Dispersant (product name " PX 4310", BASF): 1 part by weight;

[0069] ·Leveling agent (product name " F101", Taier Chemical): 0.5 parts by weight;

[0070] Isopropyl alcohol: 24.5 parts by weight;

[0071] Methyl ethyl ketone: 20 parts by weight;

[0072] Butyl acetate: 20 parts by weight.

[0073] (2) Preparation of wear-resistant coating:

[0074] The following raw materials are mixed evenly to obtain a wear-resistant coating.

[0075] Acrylic resin (product name "LUXYDIR CH-S-1257", DIC): 25 parts by weight;

[0076] Inorganic particle dispersion: 7 parts by weight;

[0077] Photoinitiator (product name "Irgacure 184", BASF): 2 parts by weight;

[0078] Leveling agent (product name "Tech-1877", Shanghai Tiger): 0.5 parts by weight;

[0079] Methyl ethyl ketone: 35.5 parts by weight;

[0080] Methyl isobutyl ketone: 30 parts by weight.

[0081] (3) Film coating:

[0082] A PET base film with a thickness of 50 μm was selected as the substrate layer. The anti-glare coating was firstly coated on one surface of the substrate layer and photocured to form an anti-glare layer. Then, a wear-resistant coating was coated on the surface of the anti-glare layer and photocured to form a wear-resistant layer to obtain an anti-glare hardened film.

[0083] The differences between the embodiments and the comparative examples are shown in Table 1 below.

[0084] Table 1 Differences between Examples and Comparative Examples

[0085]

[0086] The anti-glare hardened films of various embodiments and comparative examples were tested and analyzed.

[0087] 1. Adhesion test method:

[0088] According to the standard ASTMD 3359, first use a grid knife to draw a grid on the surface of the film layer, then stick 3M600 tape on the drawn grid, and then quickly tear off the tape in a 180° direction to observe the grid peeling condition.

[0089] 5B: The coating is not detached at all;

[0090] 4B: The coating peeling area is less than 5%;

[0091] 3B: The coating peeling area is 5% to 15%;

[0092] 2B: The coating peeling area is 15% to 35%;

[0093] 1B: The coating peeling area is 35% to 65%;

[0094] 0B: The coating peeling area is >65%.

[0095] 2. Anti-glare effect test method:

[0096] The prepared anti-glare hardened film is pasted on a black acrylic plate with the wear-resistant layer facing upwards. After repeated inspection under a three-wavelength lamp tube, the clearer the lamp tube outline on the film surface, the worse the anti-glare property; conversely, the better the anti-glare property.

[0097] Judgment criteria: If the outline of the lamp tube is evenly diffused, the anti-glare property is excellent, which is recorded as "◎"; if the outline of the lamp tube is vaguely visible, the anti-glare property is average, which is recorded as "△"; if the outline of the lamp tube is clearly visible, the anti-glare property is poor, which is recorded as "×".

[0098] 3. Haze test method:

[0099] The test was conducted using a NDH 2000N haze meter from Nippon Denshoku.

[0100] The haze of the anti-glare layer is also tested using this method.

[0101] 4. Clarity test method:

[0102] The transmitted image clarity of the antiglare cured film at 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm and 2.0 mm optical combs was measured by transmission measurement using an image clarity meter ICM-1T (manufactured by SUGA TEST INSTRUMENTS) in accordance with JIS K7105, and the total was calculated.

[0103] The clarity of the anti-glare layer is also tested using this method.

[0104] 5. Wear resistance test method:

[0105] Press Bonston steel wool #0000, 2cm×2cm wear-resistant head, against the coating surface of the film with a load of 1000g and move back and forth several times, then observe the damage state of the film surface and make a judgment.

[0106] The test results are shown in Table 2 below.

[0107] Table 2 Test results of various embodiments and comparative examples

[0108]

[0109]

[0110] Combining the results of Table 1 and Table 2, it can be seen that Examples 1 to 4 of the present application can significantly improve the wear resistance of the overall surface by controlling the ratio of the minimum protrusion height D-H1 of the organic particles relative to the anti-glare layer to the thickness H2 of the wear-resistant layer to 1.5 to 2.0, which can achieve 2000 times without scratches; and can also ensure low haze, high clarity, and anti-glare effect.

[0111] The ratio of Comparative Examples 1, 4 and 6 is too large, which is mainly manifested as poor wear resistance, and may also show poor haze and poor clarity; the ratio of Comparative Examples 2 to 3 and 5 is too small, which is mainly manifested as poor anti-glare effect, and may also show poor wear resistance.

[0112] In summary, the anti-glare hardened film and the electronic device according to the embodiments of the present application have both excellent anti-glare effect and wear resistance.

[0113] The above description is only an embodiment of the present application and is not intended to limit the protection scope of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An anti-glare hardened film, characterized in that: It comprises a substrate layer, an anti-glare layer and a wear-resistant layer stacked in sequence from bottom to top, the anti-glare layer contains organic particles, the upper half of the organic particles protrude and embed in the wear-resistant layer; the thickness of the anti-glare layer is H1, the thickness of the wear-resistant layer is H2, the diameter of the organic particles is D, And X=1.5~2.

0.

2. The anti-glare hardened film according to claim 1, characterized in that: The haze of the anti-glare layer is 50-90%, and can be 60-80%; And / or, the clarity of the anti-glare layer is 30-100%, optionally 40-90%, further optionally 50-80%; And / or, the haze of the anti-glare hardened film is 1 to 6%; And / or, the clarity of the anti-glare hardened film is 250-450%.

3. The anti-glare hardened film according to claim 1, characterized in that: The material of the organic particles includes one or more of polyacrylate, polystyrene, and polymethacrylate; And / or, the average particle size of the organic particles is 2 to 5 μm.

4. The anti-glare hardened film according to claim 1 or 3, characterized in that: The thickness H1 of the anti-glare layer is 0.5-3 μm, and the thickness H2 of the wear-resistant layer is 0.3-2 μm.

5. The anti-glare hardened film according to claim 1, characterized in that: The formula of the anti-glare coating corresponding to the anti-glare layer includes, by weight: 20 to 40 parts by weight of polyurethane acrylate; 1 to 10 parts by weight of organic particles; 1 to 5 parts by weight of photoinitiator; 0.1 to 1 parts by weight of leveling agent; 1 to 5 parts by weight of dispersant; and 40 to 70 parts by weight of organic solvent.

6. The anti-glare hardened film according to claim 5, characterized in that: The functionality of the polyurethane acrylate is 2 to 10 and the molecular weight is 1000 to 20000; The photoinitiator includes one or more of 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, benzoin dimethyl ether, xylene ketone, 2-isopropylthioxanthone, 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide, and TPO; The organic solvent includes one or more of ethyl acetate, butyl acetate, methyl ether, propylene glycol methyl ether, methyl isobutyl ketone, butanone, cyclohexanone, n-butanol, n-propanol, isopropanol, toluene and xylene.

7. The anti-glare hardened film according to claim 1, characterized in that: The formula of the wear-resistant coating corresponding to the wear-resistant layer includes, by weight: 10 to 40 parts by weight of polyurethane acrylic resin; 1 to 10 parts by weight of inorganic particles; 1 to 5 parts by weight of photoinitiator; 0.1 to 2 parts by weight of leveling agent; and 60 to 90 parts by weight of organic solvent.

8. The anti-glare hardened film according to claim 7, characterized in that: The functionality of the polyurethane acrylic resin is 6 to 15, and the molecular weight is 1000 to 20000; The inorganic particles include one or more of silicon dioxide, aluminum oxide, zinc oxide, magnesium oxide, calcium carbonate, magnesium carbonate, aluminum hydroxide and titanium dioxide, and the average particle size of the inorganic particles is 1 to 100 nm; The photoinitiator includes one or more of 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, benzoin dimethyl ether, xylene ketone, 2-isopropylthioxanthone, 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide, and TPO; The organic solvent includes one or more of ethyl acetate, butyl acetate, methyl ether, propylene glycol methyl ether, methyl isobutyl ketone, butanone, cyclohexanone, n-butanol, n-propanol, isopropanol, toluene and xylene.

9. The anti-glare hardened film according to claim 1, characterized in that: The material of the substrate layer includes one or more of polyethylene terephthalate resin, polycarbonate, triacetyl cellulose and polymethyl methacrylate; And / or, the thickness of the substrate layer is 25 to 200 μm.

10. An electronic device, characterized in that: It comprises the anti-glare hardened film according to any one of claims 1 to 9, wherein the anti-glare hardened film is arranged on the screen surface of the electronic device, and the wear-resistant layer faces upward.